Physical properties of normal grade biodiesel and winter grade biodiesel - Sadrolhosseini, Amir Reza; Abd. Moksin, Mohd Maarof; Lau, Harrison Lik Nang; Noroozi, Monir; Mat Yunus, Wan Mahmood; Zakaria, Azmi (MDPI AG, 2011)
In this study, optical and thermal properties of normal grade and winter grade palm oil biodiesel were investigated. Surface Plasmon Resonance and Photopyroelectric technique were used to evaluate the samples. The dispersion curve and thermal diffusivity were obtained. Consequently, the variation of refractive index, as a function of wavelength in normal grade biodiesel is faster than winter grade palm oil biodiesel, and the thermal diffusivity of winter grade biodiesel is higher than the thermal diffusivity of normal grade biodiesel. This is attributed to the higher palmitic acid C(16:0) content in normal grade than in winter grade palm oil biodiesel.